2014
DOI: 10.1371/journal.pone.0090645
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Region-Specific Expression of MeCP2 Isoforms Correlates with DNA Methylation within Mecp2 Regulatory Elements

Abstract: MeCP2 is a critical epigenetic regulator in brain and its abnormal expression or compromised function leads to a spectrum of neurological disorders including Rett Syndrome and autism. Altered expression of the two MeCP2 isoforms, MeCP2E1 and MeCP2E2 has been implicated in neurological complications. However, expression, regulation and functions of the two isoforms are largely uncharacterized. Previously, we showed the role of MeCP2E1 in neuronal maturation and reported MeCP2E1 as the major protein isoform in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 77 publications
7
126
0
1
Order By: Relevance
“…Recently, we showed that DNA methylation at the REs found within the Mecp2 promoter and intron 1 correlated with the dynamic expression of Mecp2 in differentiating neural stem cells (NSC) and in response to a DNA demethylating drug Decitabine (also called 5-Aza-2′-deoxycytidine) . Recently, our studies in adult murine brain regions demonstrated a correlation between the expression of Mecp2 and DNA methylation at the Mecp2 REs in vivo (Olson et al, 2014). In this current report, we studied whether DNA methylation at these reported Mecp2 REs within the promoter and intron 1 contributes in deregulating Mecp2 expression induced by ethanol.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Recently, we showed that DNA methylation at the REs found within the Mecp2 promoter and intron 1 correlated with the dynamic expression of Mecp2 in differentiating neural stem cells (NSC) and in response to a DNA demethylating drug Decitabine (also called 5-Aza-2′-deoxycytidine) . Recently, our studies in adult murine brain regions demonstrated a correlation between the expression of Mecp2 and DNA methylation at the Mecp2 REs in vivo (Olson et al, 2014). In this current report, we studied whether DNA methylation at these reported Mecp2 REs within the promoter and intron 1 contributes in deregulating Mecp2 expression induced by ethanol.…”
Section: Introductionmentioning
confidence: 82%
“…RNA was converted to cDNA with a reaction set up containing Superscript III Reverse Transcriptase (Invitrogen) using previously described methods (Kobrossy et al, 2006;Liyanage et al, 2013;Nolte et al, 2006;Rastegar et al, 2004). Quantitative RT-PCR was performed using SYBR Green-based RT 2 qPCR Master Mix (Applied Biosystems) in a Fast 7500 Real-Time PCR machine (Applied Biosystems) as previously described (Barber et al, 2013;Liyanage et al, 2013;Olson et al, 2014). Transcript levels of Mecp2 and cell type-specific markers were examined using primers listed in Table 1.…”
Section: Quantitative Real Time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
See 3 more Smart Citations